DIGITAL LIBRARY DEVELOPMENT AT MAN 1 BUKITTINGGI AS AN ACCESSIBILITY CONVENIENCE SUPPORT FOR USERS - Erlin Fitria; Ahmad Sabandi; Irsyad Irsyad; Hanif Al Kadri; Agus Nur Khomarudin (STMIK Royal, 2023)
Abstract: A digital library is a service system that capable in supporting access to information objects automatically using a computer technology. In this study, the authors aimed to develop a digital library application based on SLiMS 9 bulian at MAN 1 Bukittinggi library, especially in terms of content with the addition of e-book features, and changing the character of its applications into mobile version, which were previously local (intranet). The methods used were research and development, while system development used the Waterfall model. This study succeeded to develop a digital library application based on SLiMS 9 at MAN 1 Bukittinggi library. The development of the digital library in this study has been carried out through testing, including three types of product tests, namely validity test, practicality test, and effectiveness test, each of which was tested using a questionnaire instrument. The product validity test obtained an average value of 0.88 in the valid category; the product practicality test obtained an average value of 0.90 in the very practical category; and the product effectiveness test obtained an average value of 0.94 in the high effectiveness category. Based on the product test results that have been described, the digital library development product in this study was declared feasible and applicable as a digital library, and can be accessed via mobile by users, such as students, teachers, and library members of MAN 1 Bukittinggi. Keywords: Digital Library; Mobile Application; Research and Development; SLiMS 9 Abstrak: Perpustakaan digital merupakan sebuah sistem yang memiliki layanan yang mendukung akses objek informasi secara otomasi menggunakan teknologi komputer. Dalam studi ini, peneliti bermaksud mengembangkan aplikasi perpustakaan digital berbasis SLiMS 9 bulian pada perpustakaan MAN 1 Bukittinggi, khususnya dari sisi content-nya dengan penambahan fitur e-book, serta mengubah sifat aplikasinya menjadi bersifat mobile, yang mana sebelumnya bersifat lokal (intranet). Metode dalam studi ini adalah penelitian dan pengembangan, sedangkan pengembangan sistem dilakukan menggunakan model Waterfall. Penelitian ini berhasil mengembangkan aplikasi perpustakaan digital berbasis SLiMS 9 pada perpustakaan MAN 1 Bukittinggi. Pengembangan perpustakaan digital dalam penelitian ini telah dilakukan melalui pengujian, meliputi tiga jenis uji produk, yaitu uji validitas, uji praktikalitas, dan uji efektivitas, yang setiap pengujiannya dilakukan menggunakan instrumen angket. Uji validitas produk memperoleh nilai rerata 0,88 dengan kategori Valid; uji praktikalitas produk memperoleh nilai rerata 0,90 dengan kategori Sangat Praktis; dan uji efektivitas produk memperoleh nilai rerata 0,94 dengan kategori Efektivitas Tinggi. Berdasarkan hasil uji produk yang telah diuraikan, produk pengembangan perpustakaan digital dalam penelitian ini dinyatakan layak dan dapat diterapkan sebagai perpustakaan digital, serta dapat diakses secara mobile oleh para pengguna, yaitu siswa, guru, dan anggota perpustakaan MAN 1 Bukittinggi.Kata kunci: Aplikasi Mobile; Perpustakaan Digital; Penelitian dan Pengembangan; SLiMS 9